A case of misdiagnosis of mild cognitive impairment: The utility of symptom validity testing in an outpatient memory clinic. Issue 3 (3rd May 2016) - Roor, Jeroen J.; Dandachi-FitzGerald, Brechje; Ponds, Rudolf W. H. M.
ABSTRACT: Noncredible symptom reports hinder the diagnostic process. This fact is especially the case for medical conditions that rely on subjective report of symptoms instead of objective measures. Mild cognitive impairment (MCI) primarily relies on subjective report, which makes it potentially susceptible to erroneous diagnosis. In this case report, we describe a 59-year-old female patient diagnosed with MCI 10 years previously. The patient was referred to the neurology department for reexamination by her general practitioner because of cognitive complaints and persistent fatigue. This case study used information from the medical file, a new magnetic resonance imaging brain scan, and neuropsychological assessment. Current neuropsychological assessment, including symptom validity tests, clearly indicated noncredible test performance, thereby invalidating the obtained neuropsychological test data. We conclude that a blind spot for noncredible symptom reports existed in the previous diagnostic assessments. This case highlights the usefulness of formal symptom validity testing in the diagnostic assessment of MCI.